Dynamic Compressive Characteristics of Sandstone under Confining Pressure and Radial Gradient Stress with the SHPB Test - Shiming Wang; Yunsi Liu; Jian Zhou; Qiuhong Wu; Shuyi Ma; Zhihua Zhou (Advances in Civil Engineering)
Research on the dynamic compressive characteristics of sandstone under radial gradient stress and confining pressure is conducive to understanding the characteristics of the surrounding rock, especially in an excavation operation for an underground mine roadway and tunnel. The present work aimed at studying the effects of radial gradient stress and confining pressure on the impact of compression of sandstone using a large-diameter split Hopkinson pressure bar. The results showed that the dynamic strength of sandstone under radial gradient stress increased with strain rate following a power function, and the dynamic strength of the sandstone under radial gradient stress was lower and more sensitive to strain rate. The increase in strain at peak stress (peak strain) was linearly correlated with the strain rate under different confining pressures. The sensitivity of the peak strain to confining pressure was lower for the sandstone with a hole, while the values of the elastic modulus were decreased. However, further increasing the stain rate would lead to an increase in the elastic modulus. Also, the ductility of the sandstone with a hole tested in this study was found to improve more significantly. Finally, with an increase in the incident energy, the absorbed energy per unit volume would increase, but would not be affected obviously by the radial gradient stress.